Coastal Batik Ornament Design : Aesthetic Analysis and Meaning of Batik Ornaments in Ciwaringin Cirebon, West Java - Nanang Ganda Prawira; Mega Fitriani Adiwarna Prawira; Eko Susanto (Institut Seni Indonesia Denpasar, 2020)
Along the coast of the island of Java, there is a wealth of craft art (batik), characterized by its expression of decorative motifs and techniques. In general, the most prominent characteristic of the dominance of primary and secondary colors. Courage in expressing bright colors is also the visual identity of coastal batik. In West Java, Cirebon is one of the popular coastal batik cities. Several villages have become centers for batik crafts, including Ciwaringin Village. The batik that is developed in this village has the characteristics of Cirebon which was born and developed in line with Trusmi batik. Ciwaringin batik is unique in terms of coloring and decorative motifs when compared to Trusmi batik. In terms of typical Ciwaringin coloring is produced by natural dyes (natural dyes), a batik tradition that has long developed in the Cirebon Pesisiran batik culture. This study uses descriptive-qualitative methods with aesthetic and semiotic approaches to reveal the aesthetics and meaning of ornamentation in Batik Ciwaringin. One of the important findings in this study is that in Ciwaringin batik there is no expression of animate motives, which differentiates it from batik motifs in general because Ciwaringin batik was born from the Islamic boarding school community with strong Islamic values. Another finding is that Ciwaringin batik craftsmen transform nature not only as a source of philosophical ideas, but they also care about environmental issues. Concern for the environment is proven by developing coloring techniques using natural dyes (natural dyes) and avoiding synthetic (chemical) dyes.